The Multidimensional Nature of the Company's Competitiveness in Poland - Sebastian NAROJCZYK; Dariusz NOWAK (Communications of International Proceedings, 2021)
In order to survive and adapt to changes in the economy, enterprises must put special emphasis on the process of building and managing the company's competitiveness. It is worth It is noting that competitiveness is a very complex and multidimensional concept, which makes it the main interest of scientists and entrepreneurs. The aim of this article is to conduct a systematizing literature study and to make a critical review of the theoretical achievements to date in the area of multidimensionality of the competitiveness of enterprises. On the basis of the research, the authors presented their own methodology of managing the company's competitiveness in a more universal and complete way.
Keywords: Enterprise competitiveness; dimensions of competitiveness; competitive advantage; competitive potential